2019
DOI: 10.1111/apa.15077
|View full text |Cite
|
Sign up to set email alerts
|

Pain‐related increase in serotonin transporter gene methylation associates with emotional regulation in 4.5‐year‐old preterm‐born children

Abstract: Aim. The main goal of this study was to assess the association between pain-related increase in serotonin transporter gene (SLC6A4) methylation and emotional dysregulation in 4.5-year-old preterm children compared to full-term matched counterparts.Methods. Preterm (n=29) and full-term (n=26) children recruited from two Italian hospitals were followed-up from October 2011 to December 2017. SLC6A4 methylation was assessed from cord blood at birth from both groups and peripheral blood at discharge for preterm one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 31 publications
1
28
1
1
Order By: Relevance
“…The saliva was collected from both mothers and infants using the OraCollect for Pediatrics kit OC-175 (DNA Genotek, Ottawa, Canada) between 6 and 24 h from delivery. Methylation assessment was conducted according to previous validated procedures from this lab 27 , 28 . The genomic DNA was extracted following manufacturer’s protocols and its quality was assessed using a Qubit fluorometer Invitrogen, Thermo Fisher Scientific, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The saliva was collected from both mothers and infants using the OraCollect for Pediatrics kit OC-175 (DNA Genotek, Ottawa, Canada) between 6 and 24 h from delivery. Methylation assessment was conducted according to previous validated procedures from this lab 27 , 28 . The genomic DNA was extracted following manufacturer’s protocols and its quality was assessed using a Qubit fluorometer Invitrogen, Thermo Fisher Scientific, Waltham, Massachusetts, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a recent study found that VPT children displayed greater anger in response to an emotional stress procedure at 4.5 years compared with full‐term age‐matched controls. Remarkably, in the VPT children sample, the degree of anger expression was significantly predicted by increased SLC6A4 methylation measured at NICU discharge (Provenzi, Fumagalli, et al., 2020). Furthermore, higher exposure to pain‐related stress during NICU stay predicted an increased SLC6A4 methylation in 7‐year‐old VPT children (Chau et al., 2014), which in turn was related to internalizing behaviors.…”
Section: Introductionmentioning
confidence: 94%
“…Epigenetic mechanisms, functional modifications of the DNA that regulate gene activity without changing the DNA sequence, may explain, at least partially, how early NICU‐related stressful experiences can affect the developmental trajectories of preterm infants (Maddalena, 2013). Emerging evidence suggests a link between variation in the serotonin transporter gene (i.e., SLC6A4 ) and altered developmental trajectories of stress responses in VPT infants (Montirosso, Provenzi, Fumagalli, et al., 2016; Provenzi, Fumagalli, et al., 2020). Research on human infants indicates that postnatal maternal touch may buffer the early epigenetic effects of less‐than optimal caregiving (Murgatroyd et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…He receives the award for his paper: Pain ‐ related increase in serotonin transporter gene methylation associates with emotional regulation in 4 . 5 ‐ year ‐ old preterm ‐ born children published in Acta Paediatrica 2020 1 . The paper reports that preterm infants exposed to pain showed increased anger response to emotional stress four years later.…”
Section: Figurementioning
confidence: 99%